2022
DOI: 10.3390/ijms232113360
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Induces Apoptosis in Mouse Neonatal Testes Organ Culture

Abstract: Chemotherapy is used for childhood cancer but may lead to infertility in patients. Spermatogonia stem cells are present in the testes of prepubertal boys, although they do not produce sperm at this age. Herein, we evaluated the toxicity of cisplatin, a known medicine for cancer treatment, in neonatal mouse testes using in vitro organ culture. Mouse testicular fragments (MTFs) derived from 5.5-d postpartum mouse testes were exposed to 1–10 μg/mL cisplatin. The results showed that cisplatin significantly downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Therefore, in this study, cisplatin-induced oxidative stress was studied in testicular organ cultures in vitro. This model was reported in our previous study (Park et al, 2022).…”
Section: Bse Suppressed the Cisplatin-induced Reduction In Antioxidan...mentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, in this study, cisplatin-induced oxidative stress was studied in testicular organ cultures in vitro. This model was reported in our previous study (Park et al, 2022).…”
Section: Bse Suppressed the Cisplatin-induced Reduction In Antioxidan...mentioning
confidence: 87%
“…MTFs were cultured as described previously (Park et al, 2020b). Further, ROS generation was induced in the testes by cisplatin, and the cisplatin concentration was determined according to our previous study (Park et al, 2022). In brief, MTFs were cultured with 5 μg/mL cisplatin and 1 mg/mL BSE for five days.…”
Section: Preparation and Culture Of Mouse Testis Fragments (Mtfs)mentioning
confidence: 99%
“…One of the challenges for difficulty in preclinical to clinical translation of testicular toxicity can be attributed to the physiological and metabolic differences between the species. With the cutting-edge technologies such as 'organs-on-chips' (Zommiti et al 2022) that can emulate the human organ's physiological environment and function, there is potential to enhance our understanding of the translatability of biomarker miRNAs from nonclinical to clinical settings (Akinjo et al 2018;Park et al 2022). Leveraging such emerging tools will enable biomarker discovery, validation and clinical translation for regulatory qualification and implementation for a specific context of use in drug development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Park et al. have further demonstrated that 1–10 μg/mL of cisplatin increases the expression of pro‐apoptotic genes ( BAX , BAD , FAS , and TRAF3 ), leading the authors to hypothesize that damage was mediated by ROS accumulation 118 . Recently, a study has shown that only high cisplatin concentrations of 12–40 μg/mL can induce persistent germ cell loss and impair the in vitro spermatogenesis process 119…”
Section: Preclinical Evidence Of Testicular Damagementioning
confidence: 99%